Modifikasi Desain PID Controller Pada Permanent Magnet Synchronous Motor Dengan Flower Pollination Algorithm - Muhammad Ruswandi Djalal; Machrus Ali; Andi Imran; Herlambang Setiadi (Jurnal Teknik Elektro, 2017)
The use of PID (Proportional-Integral-Derivative) controllers on a synchronous motor is very widely used, because of its simple, robust structure that is robust and easy to use. The use of PID controllers requires proper parameter setting for optimal performance on the motor. The most commonly used solution is the trial-error method, to determine the proper parameters for PID, but the results do not make the PID controller optimal. Lately there has been a lot of research to optimize PID controller, wrong with smart method. For this purpose, we will use Flower Pollination Algorithm (FPA) optimization method to optimize and determine the exact parameters of PID. FPA is one method that is being adapted from the process of plant pollination, so this concept is adapted and applied to be. From the results that have the FPA method can be well tuned parameters PID, so that the resulting overshoot faster and settling time is very fast. Optimization results Kp 0.9441, Ki 0.9311, Kd 0.0840. In this study will discuss uncontrolled motors, with PID trial-error controller, PID-PSO and PID-FPA.Keywords: Sync motor, PID, Trial-Error, PSO, FPA, Overshoot, Settling time